Landscapes, settlers, and workforce in colonial Catamarca (Northwestern Argentina, 16th-18th c.). A historical archaeology project - Retamero, Félix; Quesada, Marcos N. (Frontiers in Environmental Archaeology, 2024)
This paper presents a collaborative work on the impact of the European colonization on the construction and management of agropastoral landscapes in Eastern Catamarca (Northwestern Argentina). This research forms part of a broader project that includes case studies from Iberian contexts from the late medieval period onward. Every colonial experiences studied so far were founded on the destruction or severe transformation of the existing society, beginning with the population itself, and the productive areas. The understanding of the new colonial order requires knowledge of the previous conditions upon which further destruction and construction coexisted, as well as the adaptative tools managed both of the indigenous population and of the colonisers. In spite of the local diversity of the new societies, some common trends can be identified in the previous peasant organizations elsewhere and in the aims and methods of the colonisation. We present the main characteristics of the población process of eastern Catamarca, both in the central valley and in the mountain range then known as Sierra de Santiago (present day El-Alto-Ancasti), between the late 16th and 18th centuries. Using both textual and archaeological evidence, we analyze how the new colonial landscapes and practices were constructed, focusing mainly on the procedures of dispossession. One of the main conclusions of the work is that, despite the initial and decisive importance of European-origin livestock in indigenous dispossession the consolidation of the conquest demanded the establishment of settlers who were also farmers. We will present three cases of settlement related to agricultural development involving people initially arriving from afar: on one hand, displaced people resettled in an estancia, family groups formed from ingas who arrived with the Spaniards in the16th century from Peru and settled in the Sierra de Santiago, and a community of African-origin slaves associated with the irrigation system in the valley of Catamarca. People of regional, Andean and African origins participated in the consolidation of the new order after being dispossessed and displaced from their places of origin. Finally, we propose some lines of future work, taking into account mainly an archaeological perspective.